Corythoichthys quattuordecim, a new pipefish (Teleostei, Syngnathidae) from the Coral Sea - Daijiro Yuki; Ronald Fricke; Hiroyuki Motomura (ZooKeys, 2025)
A new species of pipefish, Corythoichthys quattuordecim sp. nov., is described based on five specimens collected from Vanuatu and the Chesterfield Islands, New Caledonia. The species inhabits relatively deeper waters (56–81 m) compared to most of its congeners, which are typically found in shallower habitats. It is distinguished by a unique combination of morphological features, most notably the presence of 14 trunk rings, a rare meristic character within the genus. Additional diagnostic characters include a total of 51–52 body rings, 27 dorsal-fin rays, 5.0–5.75 subdorsal rings, and 16 or 17 pectoral-fin rays. Proportional traits include head length 14.1–17.4% of standard length, snout length 56.5–62.9% of head length, dorsal-fin base length 48.3–54.9% of head length, and snout depth 8.3–15.3% of snout length. The opercle bears a denticulate longitudinal ridge with two or three black vertical stripes, and the dorsal fin originates behind the posterior margin of anal ring. The new species most closely resembles C. amplexus and an undescribed taxon reported by Fricke (2004) but is clearly distinguished from both based on the above characters.